Studi Komparatif tentang Pengelolaan Media Sosial sebagai Alat Diseminasi Informasi di Masa Pandemi Covid-19 - Deswarita Tripani; Muhammad Al assad Rohimakumullah (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
Abstract Social media management, of course, has its differences and challenges for each manager, especially during the pre-Covid-19 pandemic and during the Covid-19 pandemic. The Sukabumi Regency Government (Sukabumi Regency Government) has carried out these two periods in managing its social media. Social media is used by the Sukabumi Regency Government as a means of disseminating or disseminating information, especially during the Covid-19 pandemic. The purpose of this study is to describe and understand a comparative study on the management of social media of the Sukabumi Regency Government as a means of disseminating information in the pre-pandemic period and during the Covid-19 pandemic. The method used in this research is a qualitative case study method with data collection through interviews with expert informants, key informants, and supporting informants. In addition, data collection was carried out using observation at the research site and documentation. The results of this study are that the Sukabumi Regency Government manages by utilizing several social media such as Instagram, Facebook, Twitter, Youtube and Websites. In managing social media, using theory of social media management theory by Paramitha (2011) in Pakuningjati (2015) that is planning, activation and monitoring and optimization, digital communication management by Nasrullah (2021) that is planning, activity and evaluation. This study explains that the management of social media carried out by the Sukabumi Regency Government as a tool for information dissemination during the Covid-19 pandemic is not so different from the management before the Covid-19 pandemic. The difference is only implementing health protocols when management and information about Covid-19 increase. Keywords: covid-19 pandemic, information dissemination, management and social media.